Educational software reflecting two philosophical approaches to ethics education - Betty Collis; Marike Hettinga (Association for Learning Technology, 1994)
Ethics education can vary considerably in its instructional strategies based on differences in the theoretical positions underlying the approach to moral development being stressed. Two such approaches are the 'justice' approach as exemplified by Kohlberg's six stages of moral development, and the 'care ethic' approach as exemplified by Gilligan's work on empathy as a base for moral decision-making. Each of these approaches can be demonstrated through different instructional strategies in the ethics education course, but each strategy is often difficult to execute in practice, given time and resource constraints.